Experiences of Teachers in Managing Students in the Flexible Learning - Alcopra, Aidalyn; Naparan, Genesis (Unisia, 2024)
This qualitative case study explored the teachers’ experiences in managing students in flexible learning in one of the Private Schools in the Division of Ozamiz City, Philippines. Teachers’ experiences in managing students include explaining to a class using ICT and teaching in different settings. Teachers’ ways of facilitating a class include setting guidelines in class and preparing instructional materials, conducting an oral recitation, preparing a lesson guide, and applying online educational games. Moreover, the teachers' challenges include students' attention, the credibility of students’ work, and poor internet connection. Furthermore, in dealing with the challenges, teachers provide pictures and videos to nurture focus and attention, conduct remedial classes, and seek administrative support. Therefore, the flexible learning modality ensured continuity of education in challenging times.